Neolityczne przedmioty kamienne z przedwojennych badań wykopaliskowych na stanowisku nr 5 w Jordanowie Śląskim - Dreczko, Ewa; Mozgała-Swacha, Marta; Borowski, Michał; Bronowicki, Jarosław (Uniwersytet Wrocławski Instytut Archeologii, 2020)
The excavations of the multi-phase site no. 5 in Jordanów Śląski carried out before World WarII provided a rich collection of Neolithic stone tools. The collection includes a total of 46 survivedartefacts identified with the communities of the Danubian cultures, the Jordanów culture, theFunnel Beaker culture, the Globular Amphora culture, the Corded Ware culture and – in generalterms – with the younger Stone Age. The discussed tools were excavated in settlement featuresand graves, while some of them were discovered as surface finds. On the basis of macroscopic andpetrographic research authors present a chronological, typological and raw material analysis ofthis interesting collection of artefacts.